1995
DOI: 10.1055/s-0038-1653780
|View full text |Cite
|
Sign up to set email alerts
|

One Month Follow-up of Haemostatic Variables in Patients Undergoing Aortocoronary Bypass Surgery

Abstract: SummaryIt is already known that activation of the coagulation and fibrinolytic system occurs in patients undergoing cardiopulmonary bypass (CPB). We have thus studied twenty patients (10 treated with aprotinin during CPB and 10 untreated) both during the intraoperative period and during thirty days follow up. In untreated patients D-dimer levels increased 4-fold during CPB and the levels were above baseline for the whole follow up (p<0.0001). D-dimer levels were reduced in aprotinin treated patients in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 20 publications
(25 reference statements)
2
19
1
3
Order By: Relevance
“…Interestingly, no differences in terms of endothelial or platelets activation markers were observed during the surgical procedure under different extracorporeal bypass conditions. In contrast, our study showed a significant elevation of TATc, F 1C2 and PAPc levels in the CPB group, which were confirmed by previous studies by Mannucci [13] and Ovrum [12]. During and early after cardiac surgery performed with CPB the authors demonstrated marked activation of coagulation by means of elevated levels of prothrombin fragment 1.2, and of thrombinantithrombin complex followed by a marked activation of the fibrinolytic system.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, no differences in terms of endothelial or platelets activation markers were observed during the surgical procedure under different extracorporeal bypass conditions. In contrast, our study showed a significant elevation of TATc, F 1C2 and PAPc levels in the CPB group, which were confirmed by previous studies by Mannucci [13] and Ovrum [12]. During and early after cardiac surgery performed with CPB the authors demonstrated marked activation of coagulation by means of elevated levels of prothrombin fragment 1.2, and of thrombinantithrombin complex followed by a marked activation of the fibrinolytic system.…”
Section: Discussionsupporting
confidence: 91%
“…response with complete recovery of platelet function 7 days after the last dose (18). Because cardiothoracic surgery represents a major hemostatic challenge (19) and is required in upward of 15% of patients admitted to the hospital with ACS (7-9), clinicians are confronted regularly with complex decisions concerning clopidogrel cessation and surgical revascularization. In fact, data from the CRUSADE (Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes With Early Implementation of the ACC/AHA Guidelines) initiative noted that 30% of patients undergoing CABG received clopidogrel on admission for ACS, and 87% of these patients went to surgery Յ5 days from their last clopidogrel dose (9).…”
Section: Discussionmentioning
confidence: 99%
“…In operations using cardiopulmonary bypass, additional massive activation of coagulation by the contact of blood with foreign, negatively charged, nonendothelial surfaces is described with presumable consequent activation of the fibrinolytic system. 16) A very important mechanism acti- vating the coagulation-fibrinolytic system seems to be retransfusion of pericardial blood collected intraoperatively to the extracorporeal circuit, as this shed blood contains a great amount of tissue factor and tissue plasminogen activator. 17) For this reason, a strategy based on the use of biocompatible surfaces with low thrombogenicity (eg.…”
Section: Discussionmentioning
confidence: 99%